Popularization of Rodent and Dry Root Rot Control Technologies in an Adopted Village of Indian Arid Zone - Singh, Bhagwan; Tripathi, R S; Kumar, Shalander (Annals of Arid Zone, 2016)
Diseases and rodent pests are the main factors responsible for low yield of rainfed crops in arid regions. There is a considerable scope for increasing the production of pearl millet, mung bean, moth bean, clusterbean and sesame crops by adoption of technologies generated by the Central Arid Zone Research Institute. There is a need to disseminate technologies on disease and rodent management in the farming community. Therefore, a four year study (2006-2009) was taken up to popularize improved technologies in adopted village Dantiwada of Jodhpur District. Twenty nine demonstrations on clusterbean varieties (RGC-936 and RGM-112) and 15 demonstrations on moth bean varieties (CAZRI moth-1, CAZRI moth-2, CAZRI moth-3 and RMO-435) were conducted during 2006-2009 with seed treatment of Marusena-3, a bio-formulation of Bacillus firmus developed by CAZRI, Jodhpur, for controlling dry root rot disease. Plant mortality due to dry root rot in improved moth bean varieties was lower (17-23%) in treated plots as compared to 39 to 63% in untreated plots. The seed yield increased by 11-16% in improved clusterbean varieties and by 25-30% in local variety compared to control. On rodent management, 18 demonstrations on poison baiting with two rodenticide (zinc phosphide and bromadiolone as alone and also as follow up) were conducted in fields having pearl millet, mung bean, moth bean, clusterbean and sesame crops. Rodent control was successfully achieved with single treatment of zinc phosphide (2%) by 57 to 65% within 4 days of treatment. Single treatment with bromadiolone (0.005%) yielded 75 to 78% rodent control in these crops 15 days after treatment. Double baiting i.e. treatment of zinc phosphide followed by bromadiolone, the rodent control success 15 days after treatment was 82-84%. Adoption of rodenticidal treatments increased yield by 18 to 27% compared to control. Nine training programs were organized on dissemination of these technologies where 269 farmers/farm women were benefitted. Level of farmer’s knowledge about management of disease and rodent pest increased significantly by 60-65% after training and demonstration. Key words: Rodent, dry root rot, marusena, rodenticide.